"Solemate" / Izzafaiqaainaa Mohd Nor ... [et al.] - Mohd Nor, Izzafaiqaainaa; Mohd Adam, Nor Fadhilah; Che Azmi, Nurazira; Abdul Razak, Noraini (2016)
The team is introducing microchip shoes insole that provides information on body temperature, heart rate, calorie burn, insole location, and measuring daily steps during exercising. This microchip shoes insole is connected with Bluetooth and also provided with mobile application which functions to detect all the information above.